Transition-Metal-Free Easy Access to 2-(2-Oxo-2-arylethyl)-4H-chromen-4-ones from 2-Hydroxyacetophenone - Ghatak, Trisha; Althagafi, Ismail; Nath, Mahendra; Pratap, Ramendra; Yadav, Dharmendra Kumar (Synlett, 2025)
A stepwise synthetic strategy has been devised to access 2-(2-oxo-2-arylethyl)-4H-chromen-4-ones from 2-hydroxyacetophenone, offering a structurally oxidized analogue of 2-(2-phenylethyl)chromones (PECs). The key substrate, 2-(methylthio)-4H-chromen-4-one, is readily synthesized in two steps from a protected 2-hydroxyacetophenone. Under mild reaction conditions (25 °C) in DMSO/KOH, 2-(methylthio)-4H-chromen-4-one undergoes nucleophilic substitution with various arylmethyl ketones to furnish 2-(2-oxo-2-arylethyl)-4H-chromen-4-ones in moderate to good yields. The transformation exhibits broad substrate scope and excellent functional group tolerance. Notably, the resulting 2-(2-oxo-2-arylethyl)-4H-chromen-4-ones can serve as valuable intermediates for the development of medicinally and materially relevant functionalized molecules, highlighting the synthetic and applicative significance of this methodology.
Keywords: Ketene dithioacetal; chromones; arylmethyl ketones; nucleophilic substitution